Causal relationships from legume crops to soil microbial properties relative to canola. (31st December 2020) - Lupwayi, Newton Z.; Schwinghamer, Timothy D.; Tidemann, Breanne D.; Kubota, Hiroshi; Turkington, T. Kelly; Khakbazan, Mohammad; St. Luce, Mervin
Abstract: Legume crop rotational effects are usually studied in only the first subsequent non‐legume crop even though several consecutive crops usually follow a legume. We studied the effects of field pea ( Pisum sativum L.), faba bean ( Vicia faba L.), faba bean green manure (faba GM), lentil ( Lens culinaris Medik.), canola ( Brassica napus L.), and wheat ( Triticum aestivum L.), on soil microbial biomass carbon (MBC), β‐glucosidase enzyme activity, and bacterial physiological diversity in three subsequent crops at four locations. Generalized linear modeling (SAS PROC GLIMMIX) indicated that, when canola is grown 3 yr after an initial canola crop in the rotation, MBC is 4–40% (Bonferroni‐adjusted limits at 95% confidence) greater than when faba bean is the initial crop. Path modeling (SAS PROC CALIS) confirmed the negative effect on MBC by faba bean (relative to canola) as an initial crop. According to Bonferroni‐adjusted limits at 95% confidence, where faba GM was the initial crop, β‐glucosidase activity was 2–24% greater than where faba bean was the initial crop and 0.4–21.8% greater than where wheat was the initial crop. Similarly, where lentil was the initial crop, β‐glucosidase activity was 2–23% greater than where pea was the initial crop and 3–5% greater than where wheat was the initial crop. Path modeling revealed direct causal relationships from faba GM and lentil to β‐glucosidase activity. The legume crop effects on soil microbial properties were: faba GM > lentil > pea > faba bean, but we did not observe diminishing effects of the initial legumes to consecutive subsequent crops. Core Ideas: Faba bean GM increased soil MBC and β‐glucosidase activity more than faba bean grown for seed. Lentil increased β‐glucosidase activity more than other legumes except faba bean GM. The legume effects on soil microbial properties were: faba bean GM > lentil > pea > faba bean.